Lnc-PKD2-2-3/miR-328/GPAM ceRNA Network Induces Cholangiocarcinoma Proliferation, Invasion and 5-FU Chemoresistance - Zhang, Lei; Ma, Donglai; Li, Fujun; Qiu, Gongcai; Sun, Dongsheng; Zeng, Zhaolin (Frontiers in Oncology, 2022)
Purpose: Our previous study observed that long non-coding RNA PKD2-2-3 (lnc-PKD2-2-3) related to advanced tumor features and worse prognosis in cholangiocarcinoma (CCA). Then, the current study aimed to further explore the linkage of among lnc-PKD2-2-3, miR-328 and GPAM, as well as their effect on regulating CCA viability, mobility and chemosensitivity. Methods: Lnc-PKD2-2-3, miR-328 and GPAM expressions in 30 pairs of CCA tumor and adjacent tissues, as well as in CCA cell lines were determined. Two CCA cell lines (HuCCT1 and TFK1) were transfected by lnc-PKD2-2-3 overexpression plasmid, lnc-PKD2-2-3 siRNA, miR-328 inhibitor and GPAM siRNA alone or in combination, followed by cell proliferation, apoptosis, invasion and 5-FU chemosensitivity detections. Besides, xenograft mice were established for validation. Results: Lnc-PKD2-2-3 and GPAM were higher, while miR-328 was lower in CCA tissues versus adjacent tissues, also in CCA cell lines versus control cells; meanwhile, they were correlated with each other (all P<0.05). Lnc-PKD2-2-3 knockdown decreased CCA cell proliferation, invasion while increased apoptosis (all P<0.05); but lnc-PKD2-2-3 overexpression exhibited an opposite and weaker effect. MiR-328 knockdown induced CCA cell proliferation and invasion, also attenuated lnc-PKD2-2-3-knockdown’s effect on these functions (all P<0.05). Subsequently, GPAM knockdown reduced CCA cell proliferation and invasion, also weakened miR-328-knockdown’s effect on these functions (all P<0.05). In addition, lnc-PKD2-2-3 positively regulated GPAM while negatively regulated miR-328, miR-328 negatively modified GPAM in CCA cells. Luciferase gene reporter assays verified that lnc-PKD2-2-3 directly bound miR-328, miR-328 directly bound GPAM. Finally, lnc-PKD2-2-3/miR-328/GPAM network also regulated 5-FU chemosensitivity of CCA cells. In vivo experiments further revealed that lnc-PKD2-2-3 overexpression promoted tumor volume and weight, but repressed tumor apoptosis in xenograft mice; meanwhile, it increased GPAM expression while decreased miR-328 expression (all P<0.05). Reversely, lnc-PKD2-2-3 knockdown exhibited the opposite effects (all P<0.05). Conclusion: Lnc-PKD2-2-3/miR-328/GPAM ceRNA network promotes CCA proliferation, invasion and 5-FU chemoresistance.